(untitled) (LIS TODAY, 2023)
Plagiarism is a massive issue in today’s academic field due to the information overflow. It can be noticeable at every level of the academic career. Many academicians take shortcuts when working, which leads them to use plagiarism because they are unaware of plagiarism, do not want to break the copy-and-paste culture or are pressed for time. Plagiarism is when someone takes someone else’s work and passes them off as their own. Plagiarism is strongly linked to forgery and piracy, both of which are illegal under copyright laws. This is a significant problem for university students and research scientists; everyone must be extremely cautious with their academic work to solve it.This study shows the awareness of plagiarism among the students of two renowned universities in Delhi. It also shows the reason behind the adoption of plagiarism.A quantitative survey was conducted in Delhi with a sample of 100 students from Delhi University (DU) and Jawaharlal Nehru University (JNU). The first main finding of the report is that the reasons for plagiarism are a lack of willingness to study and a copy-paste culture. Second, most students learn about plagiarism through lecturers or other sources like web sources. Nowadays, plagiarism has become a punishable offence, so we need to be extra careful about plagiarism.